2022
DOI: 10.1159/000526528
|View full text |Cite
|
Sign up to set email alerts
|

Ovalbumin-Induced Epithelial Activation Directs Monocyte-Derived Dendritic Cells to Instruct Type 2 Inflammation in T Cells Which Is Differentially Modulated by 2′-Fucosyllactose and 3-Fucosyllactose

Abstract: Allergic sensitization starts with epithelial cell activation driving dendritic cells (DCs) to instruct T helper 2 (Th2) cell polarization. Food allergens trigger intestinal epithelial cell (IEC) activation. Human milk oligosaccharides may temper the allergic phenotype by shaping mucosal immune responses.We investigated in vitro mucosal immune development after allergen exposure by combining ovalbumin (OVA)-preexposed IEC with monocyte-derived DCs (OVA-IEC-DCs) and subsequent coculture of OVA-IEC-DCs with Th c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(25 citation statements)
references
References 57 publications
4
21
0
Order By: Relevance
“…The current data show that ovalbumin can provoke type 2 activation of both IEC as well as DC. Previously we confirmed that OVA-IEC could drive functional type 2 differentiation in DC, but in the latter study IEC were exposed to OVA for 24h before the IEC/moDC coculture (13). The current study shows both OVA-IEC-DC as well as OVA-DC to obtain a type 2 moDC phenotype, but their phenotype differs depending on the presence of IEC which are known to shape the innate immune response.…”
Section: Discussionsupporting
confidence: 69%
See 4 more Smart Citations
“…The current data show that ovalbumin can provoke type 2 activation of both IEC as well as DC. Previously we confirmed that OVA-IEC could drive functional type 2 differentiation in DC, but in the latter study IEC were exposed to OVA for 24h before the IEC/moDC coculture (13). The current study shows both OVA-IEC-DC as well as OVA-DC to obtain a type 2 moDC phenotype, but their phenotype differs depending on the presence of IEC which are known to shape the innate immune response.…”
Section: Discussionsupporting
confidence: 69%
“…Thus the initial presence of IEC during allergen exposure may have facilitated not only the release of type 2 activating mediators but also regulatory factors that suppressed full DC activation in this model. Yet, previous in vitro studies demonstrated a type 2 instructing effect from epithelial cells, which can be due to differences in model conditions ( 11 13 ). However, the current study shows a stronger type 2 response to OVA in absence of IEC, while OVA-IEC-DC contribute to enhanced regulatory IL-10 secretion during coculture with T cells as indicator for a more tolerogenic response to the allergen.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations